A Chemical Epitope‐Targeting Strategy for Protein Capture Agents: The Serine 474 Epitope of the Kinase Akt21. Issue 52 (19th November 2013) - Nag, Arundhati; Das, Samir; Yu, Mary Beth; Deyle, Kaycie M.; Millward, Steven W.; Heath, James R.
<x xml:space="preserve">Abstract</x> Target and click: Peptide ligands targeted to the C‐terminal motif of the kinase Akt2 were obtained by combining phosphate recognition of a dinuclear zinc(II) complex with in situ click chemistry to target this epitope. The peptide ligands (shown as XXXXX) selectively bind the C‐terminal polypeptide of Akt2, and are selective for Akt2 relative to the Akt1 and Akt3 isoforms. The ligands differentially modulate Akt2 activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>